2019
DOI: 10.5812/aapm.94654
|View full text |Cite
|
Sign up to set email alerts
|

Comparison the Effect of Active Cyclic Breathing Technique and Routine Chest Physiotherapy on Pain and Respiratory Parameters After Coronary Artery Graft Surgery: A Randomized Clinical Trial

Abstract: BackgroundThere are limited reports available on preferred chest physiotherapy methods in patients with coronary artery graft (CABG) surgery.ObjectivesThe aim of this study was to compare the effect of active cyclic breathing technique (ACBT) and routine chest physiotherapy on pain and respiratory parameters in patients undergoing CABG surgery.MethodsThis randomized clinical trial was carried out from July to November 2018. Seventy patients were selected randomly after CABG according to inclusion criteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
6
0
3
Order By: Relevance
“…There are routine physiotherapy techniques which help to improve the pulmonary function from immediate post-operative period onwards. Amongst Active cycle breathing technique in as excellent breathing exercise because of a signi icant piece of the clearance mechanism of either an episode or a cough which diminishes the atelectatic area and increase ventilation (Frownfelter and Dean, 2012;Derakhtanjani et al, 2019). Hence the current was conducted to determine the effectiveness of active cycle breathing technique on pulmonary complications and found that there is an improvement in physiological parameters which inturn reduces the postoperative pulmonary complication.…”
Section: Resultsmentioning
confidence: 99%
“…There are routine physiotherapy techniques which help to improve the pulmonary function from immediate post-operative period onwards. Amongst Active cycle breathing technique in as excellent breathing exercise because of a signi icant piece of the clearance mechanism of either an episode or a cough which diminishes the atelectatic area and increase ventilation (Frownfelter and Dean, 2012;Derakhtanjani et al, 2019). Hence the current was conducted to determine the effectiveness of active cycle breathing technique on pulmonary complications and found that there is an improvement in physiological parameters which inturn reduces the postoperative pulmonary complication.…”
Section: Resultsmentioning
confidence: 99%
“…A metaanalysis of 20 clinical cases including 3000 patients who received ASA as secondary cardiovascular prevention indicated that "aspirin resistance" in 28% of the patients correlated with a four-fold risk of CVD (20,21). ASA can be prescribed in numerous cardiovascular issues, including coronary artery bypass surgery (22)(23)(24)(25)(26), venous thrombosis, peripheral arterial disease, and cerebrovascular diseases (27)(28)(29).…”
Section: Cardiovascular Related Beneficial Effectsmentioning
confidence: 99%
“…Jumlah dan frekuensi setiap komponen ACBT dapat diubah, tetapi semua komponen siklus harus diterapkan dan bervariasi dengan kontrol respirasi. Teknik ini telah terbukti efektif dalam memobilisasi dan membersihkan kelebihan sekresi bronkial dan meningkatkan fungsi paru-paru (Maria W. Lamuvel, 2016;Derakhtanjani et al, 2019;Naseer et al, 2019). Studi kasus berbasis bukti ini bertujuan untuk mengetahui efektivitas ACBT dalam meningkatkan kemampuan fungsional paru terhadap pasien pasca operasi CABG dibandingkan dengan metode chest physiotherapy yang lain.…”
Section: Pendahuluanunclassified
“…Hasil Studi perbandingan yang dilakukan oleh Ahmad S. et al (Derakhtanjani et al, 2019), juga menunjukkan bahwa intervensi ACBT dan fisioterapi dada rutin (routine chest physiotherapy) mempunyai efek yang sama terhadap penurunan nyeri, hal ini dibuktikan dengan nilai p-value sebesar 0.001 yang berarti ACBT dan routine chest physiotherapy menunjukkan efek signifikan terhadap penurunan nyeri pada pasien post CABG.…”
Section: Masalah Klinisunclassified